1999
DOI: 10.1016/s0014-5793(99)01007-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of a bound ubiquinone on reactions of the Escherichia coli cytochrome bo with ubiquinol and dioxygen

Abstract: To probe the functional role of a bound ubiquinone-8 in cytochrome bo-type ubiquinol oxidase from Escherichia coli, we examined reactions with ubiquinol-1 and dioxygen. Stoppedflow studies showed that anaerobic reduction of the wild-type and the bound ubiquinone-free (v vUbiA) enzymes with ubiquinol-1 immediately takes place with four kinetic phases. Replacement of the bound ubiquinone with 2,6-dibromo-4-cyanophenol (PC32) suppressed the anaerobic reduction of the hemes with ubiquinol-1 by eliminating the fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 22 publications
4
12
0
Order By: Relevance
“…These results provide further support for our proposal that the Cu A end of the cupredoxin fold and the quinol oxidase specific (Qox) domain provides the Q L site and is involved in electron transfer to the metal centers in subunit 1 (15). Since the bound ubiquinone at the Q H site is essential for the quinol oxidation at the Q L site (16,18,19), the Q H site may be located in transmembrane helices of subunit II and/or subunit I.…”
Section: Resultssupporting
confidence: 72%
“…These results provide further support for our proposal that the Cu A end of the cupredoxin fold and the quinol oxidase specific (Qox) domain provides the Q L site and is involved in electron transfer to the metal centers in subunit 1 (15). Since the bound ubiquinone at the Q H site is essential for the quinol oxidation at the Q L site (16,18,19), the Q H site may be located in transmembrane helices of subunit II and/or subunit I.…”
Section: Resultssupporting
confidence: 72%
“…The protein binding site which stabilizes the semiquinone is referred to as the high affinity Q-binding site, or Q H . Stabilizing the 1-electron reduced form of the quinone is consistent with the quinone bound at this site acting as a “pair splitter”, which can be reduced by two electrons and then transfer the electrons one-at-a-time to a 1-electron acceptor, heme b [19, 20]. The rate of formation of the semiquinone upon mixing reduced ubiquinol-2 with the enzyme has been monitored by rapid freeze-quench EPR spectroscopy, and the results indicate that the semiquinone formed at the Q H -site is an intermediate in the catalytic mechanism [21].…”
Section: Introductionmentioning
confidence: 88%
“…The semiquinone at the Q H -site is formed within 10 μs after pulsed radiolysis, and electron transfer from the semiquinone to heme b follows, with a first order rate constant of 1.5 × 10 3 s −1 [22]. Studies of the reaction of the fully reduced enzyme with O 2 have shown that electron transfer from heme b to the heme o 3 /Cu B binuclear center occurs with a rate of about 10 4 s −1 [19, 23]. A comparison of the intramolecular electron transfer events for enzyme containing the quinone bound at the Q H -site with enzyme from which the quinone has been removed (prepared in Triton X-100) also supports the model that the tightly bound reduced quinone is capable of rapid electron transfer to heme b [12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant effort (17,19,20), little is known about the location of this site within the protein (21). Cyt bo 3 , when purified using the detergent dodecylmaltoside, has 1 eq of ubiquinol-8 bound at the Q H -site, and this bound quinol does not readily exchange with the free quinol in the membrane (18,(22)(23)(24). The ubiquinone bound at the Q H -site functions as a cofactor, accepting two electrons from the quinol at the Q L -site and passing the electrons on to heme b one at a time.…”
mentioning
confidence: 99%